KEKERASAN POLITIK DAN KERUSUHAN SOSIAL DALAM PEMILUKADA - Pradhanawati, Ari (Faculty of Social and Political Sciences Diponegoro University, 2011)
Abstract :Political violence during local elections (pemilukada) that had been conducted since 2005 generate unsatisfactory situation that create anarchism among civilian. This paper discuss about political violence and social riot from Sociology standpoint. It employ social definition paradigm by focusing on the Theory of Communication Action by Jurgen Habermas. This article explain that the social riot/ anarchism is caused by the lack of citizen' maturity and understanding about how to conduct a 'good' political communication. This situation also reflect the level of rationality of Indonesian people in term of its maturity to respond political issue. This discussion conclude that there is an unbalance cross-communication among stakeholders that ultimately lead to form structural anarchism. To overcome this problem, the author offer a concept of communicative society that expectantly become an alternative method to develop new consensus for running political process in order to reduce the violence and social riot in the general election.Â Key Words Â : political violence; social riot; local electionpermalink:Â http://ejournal.undip.ac.id/index.php/forum/article/view/3151